1994
DOI: 10.1136/bjsm.28.4.276
|View full text |Cite
|
Sign up to set email alerts
|

Badminton injuries--a prospective epidemiological and socioeconomic study.

Abstract: During a 1-year period 100 badminton players were registered and treated in the casualty ward of Randers City Hospital, Denmark. The injuries to the badminton players constituted 5% of all sports injuries registered during the same period in the casualty wardl'2. At follow-up questionnaires were sent to all participants. Replies were received from 89 patients. Over the same period all sports participants in the hospital catchment area (30 254) were registered according to their sport affiliation (2620 badminto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
76
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 10 publications
3
76
1
1
Order By: Relevance
“…As an example, the FIFA 11+ warm-up programme, is designed to reduce lower limb injuries, including ACL injuries, among football players aged 14 years and older (http://f-marc.com/11plus/home/). The greater proportion of some injuries in males in the current study was similar to that in previous work [11,13,14]; nevertheless participation rate was not accounted for as gender participation numbers were not available from Badminton New Zealand. In studies where an elite sample [15] and community participation [12] were adjusted for, the risk of injuries to males and to females was comparable.…”
Section: Injured Players' Characteristicssupporting
confidence: 76%
See 4 more Smart Citations
“…As an example, the FIFA 11+ warm-up programme, is designed to reduce lower limb injuries, including ACL injuries, among football players aged 14 years and older (http://f-marc.com/11plus/home/). The greater proportion of some injuries in males in the current study was similar to that in previous work [11,13,14]; nevertheless participation rate was not accounted for as gender participation numbers were not available from Badminton New Zealand. In studies where an elite sample [15] and community participation [12] were adjusted for, the risk of injuries to males and to females was comparable.…”
Section: Injured Players' Characteristicssupporting
confidence: 76%
“…Other authors have also reported age as a risk factor for badminton (Table 3). Previous studies using data across performance levels have presented three age-bands: under 16, 16-25 and above 25 [11]; or under 18, 18-25 and above 25 years old [12,13]. Although the greater number of injuries was seen in the higher age-groups, the results lack specificity due to a much wider age range of 7-57 years [12] and 10-60 years [13].…”
Section: Injured Players' Characteristicscontrasting
confidence: 44%
See 3 more Smart Citations